PERANAN ORGANISASI SOSIAL KEMASYARAKATAN DALAM UPAYA MENGOPTIMALKAN PEMUNGUTAN PBB DI KABUPATEN LOMBOK BARAT - PUTU KARISMAWAN; I DEWA KETUT YUDA SENOPATI; A.A SURYA KENCANA (Universitas Mahasaraswati K. Mataram, 2023)
Tax is the most state income in Indonesia. Land and Building Tax (PBB) is one of the regency/city taxes wich is a component of Regency/Citu original egency/City Revenue (PAD. In Some area the contribution of PBBto PAD is still relatively small. The small contibution of PBB to PADis due to the lack of awarenessof taxpayersto pay PBB before majurity even taxpayers often forget to pay PBB. Varioue efort have been made by the government in order to optimized state revenues from taxes, both throughtax collection intensification programs and extensification programs, such as the tax amnesty wich was recently implemented by the government. The sucses of the efforts made by the government on the one hand is highly dependent on the dedication, the integrity of tax officers, on the other hands, it depends on the participation all of tax payers.